Konsep Negara Kesatuan Republik Indonesia Mencegah Konflik Politik Menuju Persatuan Indonesia di Era Digital - M Zebin Ardhani; Diki Wilda Rinta; Ivan Adhitheo Prayoga; Linda Amani Sujana; Muhammad Farzani (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
In the rapidly developing digital era, the concept of the Unitary State of the Republic of Indonesia (NKRI) has an increasingly important role in preventing political conflict and strengthening national unity. As a country consisting of various tribes, religions, cultures and diverse backgrounds, Indonesia is faced with great challenges in maintaining its integrity and stability. Political conflict is one of the threats that can threaten national unity and integrity, especially in a digital context which allows information to spread quickly and widely without geographical boundaries. In the complexity of current political dynamics, the concept of the Republic of Indonesia is not just an empty slogan, but a real guideline in maintaining the unity and integrity of the nation. By building collective awareness of the importance of unity, Indonesia can face the challenges of the digital era more firmly. The aim of this scientific article is to explain the role of the concept of the Unitary State of the Republic of Indonesia (NKRI) in preventing political conflict in the digital era and to analyze the challenges and threats faced in maintaining the unity of the Indonesian nation amidst the dynamics of the digital era.